Thematic cartography and remote sensing - Nag, Prithvish; Dutt, G. K. 1929-. (New Delhi Concept Pub. Co., 1992)
Festschrift honoring G.K. Dutt, b. 1929, geographer from India; comprises contributed articles in the Indian context.
Includes index.
Includes bibliographical references (p. [261]-263).
Keywords: Dutt, G. K. -- 1929-.; Cartography; Remote sensing